A Survey on One Health Approach in Colombia and Some Latin American Countries: From a Fragmented Health Organization to an Integrated Health Response to Global Challenges - Cediel Becerra, Natalia Margarita; Olaya Medellin, Ana María; Tomassone, Laura; Chiesa, Francesco; De Meneghi, Daniele (Frontiers in Public Health, 2021)
The “One Health” (OH) approach has been recognized by world health authorities such as FAO/OIE/WHO, advocating for effective, multi-sectoral, and transdisciplinary collaboration. However, there is a lack of published evidence of the awareness of the OH concept in Colombia and other countries in the Latin American Region. In order to explore existing collaboration amongst the animal health, human-public health, environmental health sectors, and to describe the perception, knowledge, and barriers on OH in Colombia and other countries of Latin America, an online questionnaire-based survey was distributed among key professionals representing the three OH pillars (August 2018–August 2020). Overall, 76 key respondents from 13 countries (Colombia, México, Chile, Brazil, Argentina, Bolivia, Costa Rica, Ecuador, Perú, Guatemala, Nicaragua Uruguay, and Venezuela) completed the questionnaire. Respondents worked in institutions of animal (59%), public (20%), human (7%), and environmental health (7%); they mainly belonged to higher academic institutions (59%), followed by ministries (11%), and research organizations (9%). Most participants (92%) were familiar with the OH term and 68% were aware of the formal cooperation among sectors in their countries, mostly on zoonoses; in 46% of the cases, such connections were established in the last 5 years. The main reported limiting factors to intersectorality were the lack of commitment of policy-makers, resources, and budget for OH (38%) and the “siloed approach” of sectors and disciplines (34%). Respondents ranked a median score of 3.0 (1–5 scoring) in how good OH activities are implemented in their countries, and a median score of 2.0 in the citizen awareness on OH as regards their countries. The most important OH issues were identified in vector-borne diseases, rabies, wrong and/or improper use of antimicrobials, emerging viral diseases, food-borne diseases, neglected parasitic diseases, deforestation, and ecosystem fragmentation. Although there is a high-perceived importance on conjoint cooperation, OH implementation, and operationalization remain weak, and the environmental component is not well-integrated. We consider that integration and implementation of the OH Approach can support countries to improve their health policies and health governance as well as to advocate the social, economic, and environmental sustainability of the Region.